Ḥanafī Approaches to Copyright - Lowe, Julie (Islamic law and society, 2023)
Academic articles on Islamic law and intellectual property often mention that the Ḥanafī legal tradition is the only school that does not protect intellectual property. By examining Ḥanafī legal manuals and fatwās by contemporary Ḥanafī jurists, I argue that variant interpretations of Ḥanafī doctrine can result in a finding of compatibility or incompatibility between Ḥanafī law and copyright. Interpretations that recognize copyright protect Ḥanafīs from tension between state laws on intellectual property and religious practice. Whereas some Ḥanafī jurists hold that Ḥanafī law is fully compatible with copyright, others place restrictions on copyright or reject copyright entirely. Ḥanafī legal manuals grant some protection to intangible notions such as honour, confidentiality and sanctity. One interpretation of property rules accommodates intellectual property rights. The principles of public interest (ḥuqūq Allāh) and private rights (ḥuqūq al-ʿibād) may provide jurists who accept intellectual property with a means to better theorize aspects of copyright.